Ag-Incentives Consortium improves global data on agricultural policies - CGIAR Research Program on Policies, Institutions, and Markets (International Food Policy Research Institute, 2018)
Many governments intervene in agricultural markets. The reasons for doing so vary greatly: to keep food prices low for consumers; to support farm incomes; to reduce price volatility; and to meet other political objectives. Some policy interventions can have unforeseen consequences. Monitoring the levels of incentives in many countries provides information on changes in global markets, and measuring the impact of incentives helps governments to make necessary policy adjustments. Several international organizations have for some time been regularly monitoring agricultural incentives, but in an uncoordinated way. “Historically, global information and data on incentives for agricultural production have been widely scattered and not comparable,” says David Laborde, senior research fellow at the International Food Policy Research Institute (IFPRI). To address these issues, a group of leading international organizations joined with IFPRI and PIM in 2013 to form the Agricultural Incentives Consortium (Ag-Incentives). Ag-Incentives brings together data from the Organisation for Economic Co-operation and Development, the Food and Agriculture Organization of the United Nations, the Inter-American Development Bank, and the World Bank. IFPRI leads the harmonization and sharing of these data.